The Next Generation Fornax Survey (NGFS): VII. A MUSE view of the nuclear star clusters in Fornax dwarf galaxies. Issue 2 (9th May 2020) - Johnston, Evelyn J; Puzia, Thomas H; D'Ago, Giuseppe; Eigenthaler, Paul; Galaz, Gaspar; Häußler, Boris; Mora, Marcelo D; Ordenes-Briceño, Yasna; Rong, Yu; Spengler, Chelsea; Vogt, Frédéric; Côté, Patrick; et al.
ABSTRACT: Clues to the formation and evolution of nuclear star clusters (NSCs) lie in their stellar populations. However, these structures are often very faint compared to their host galaxy, and spectroscopic analysis of NSCs is hampered by contamination of light from the rest of the system. With the introduction of wide-field integral field unit (IFU) spectrographs, new techniques have been developed to model the light from different components within galaxies, making it possible to cleanly extract the spectra of the NSCs and study their properties with minimal contamination from the light of the rest of the galaxy. This work presents the analysis of the NSCs in a sample of 12 dwarf galaxies in the Fornax Cluster observed with the Multi-Unit Spectroscopic Explorer (MUSE). Analysis of the stellar populations and star formation histories reveal that all the NSCs show evidence of multiple episodes of star formation, indicating that they have built up their mass further since their initial formation . The NSCs were found to have systematically lower metallicities than their host galaxies, which is consistent with a scenario for mass assembly through mergers with infalling globular clusters, whilst the presence of younger stellar populations and gas emission in the core of two galaxies is indicative of in-situ star formation. We conclude that the NSCs in these dwarf galaxies likely originated as globular clusters that migrated to the core of the galaxy that have built up their mass mainly through mergers with other infalling clusters, with gas-inflow leading to in-situ star formation playing a secondary role.